Evaluating agricultural trade-offs in the age of sustainable development. (June 2018) - Kanter, David R.; Musumba, Mark; Wood, Sylvia L.R.; Palm, Cheryl; Antle, John; Balvanera, Patricia; Dale, Virginia H.; Havlik, Petr; Kline, Keith L.; Scholes, R.J.; Thornton, Philip; Tittonell, Pablo; et al.
Abstract: A vibrant, resilient and productive agricultural sector is fundamental to achieving the Sustainable Development Goals. Bringing about such a transformation requires optimizing a range of agronomic, environmental and socioeconomic outcomes from agricultural systems – from crop yields, to biodiversity, to human nutrition. However, these outcomes are not independent of each other – they interact in both positive and negative ways, creating the potential for synergies and trade-offs. Consequently, transforming the agricultural sector for the age of sustainable development requires tracking these interactions, assessing if objectives are being achieved and allowing for adaptive management within the diverse agricultural systems that make up global agriculture. This paper reviews the field of agricultural trade-off analysis, which has emerged to better understand these interactions – from field to farm, region to continent. Taking a "cradle-to-grave" approach, we distill agricultural trade-off analysis into four steps: 1) characterizing the decision setting and identifying the context-specific indicators needed to assess agricultural sustainability, 2) selecting the methods for generating indicator values across different scales, 3) deciding on the means of evaluating and communicating the trade-off options with stakeholders and decision-makers, and 4) improving uptake of trade-off analysis outputs by decision-makers. Given the breadth of the Sustainable Development Goals and the importance of agriculture to many of them, we assess notions of human well-being beyond income or direct health concerns (e.g. related to gender, equality, nutrition), as well as diverse environmental indicators ranging from soil health to biodiversity to climate forcing. Looking forward, areas of future work include integrating the four steps into a single modeling platform and connecting tools across scales and disciplines to facilitate trade-off analysis. Likewise, enhancing the policy relevance of agricultural trade-off analysis requires improving scientist-stakeholder engagement in the research process. Only then can this field proactively address trade-off issues that are integral to sustainably intensifying local and global agriculture – a critical step toward successfully implementing the Sustainable Development Goals. Highlights: Agriculture is central to the success of the Sustainable Development Goals. Trade-off analysis allows the assessment of multiple aspects of sustainability. "Cradle-to-grave" approach, from indicator selection to effective communication Better engagement with stakeholders is critical to ensure policy relevance.